2008
DOI: 10.1115/1.2885185
|View full text |Cite
|
Sign up to set email alerts
|

A Signal Grammar to Guide Functional Modeling of Electromechanical Products

Abstract: In modern product design methodologies, designers are increasingly required to combine elements spanning multiple engineering domains, thus blurring the boundaries between engineering disciplines. Functional modeling with the Functional Basis provides the basic tools required to integrate system models at the conceptual level; however, there is a lack of unified rules to address the structure of functional models. This article covers the development of a signal grammar for functional modeling with a Functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another approach to compare representations examines the vocabulary, structure, expression, purpose, and abstraction (Summers & Shah, 2004). Expanding upon that research, we propose that the representation comparison should include, but not be limited to the following: scope: the domain for which the function modeling approach is intended (Nagel, Vucovich, et al, 2008); flexibility: the ability to modify and adapt the representation to address new problems (Regli et al, 2000); indexing: support access to the right (or useful) knowledge when needed (Goel & Bhatta, 2004); consistency: enforce physics and other consistencies (Sen et al, 2011 b ); translationabilty: tied to other engineering models (Nebel, 2000); behavior: ability of the representation to simulation behavior (Qian & Gero, 1996); and scalability: support both simple and complex problem types (Chiang et al, 2001). …”
Section: Comparison Across the Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to compare representations examines the vocabulary, structure, expression, purpose, and abstraction (Summers & Shah, 2004). Expanding upon that research, we propose that the representation comparison should include, but not be limited to the following: scope: the domain for which the function modeling approach is intended (Nagel, Vucovich, et al, 2008); flexibility: the ability to modify and adapt the representation to address new problems (Regli et al, 2000); indexing: support access to the right (or useful) knowledge when needed (Goel & Bhatta, 2004); consistency: enforce physics and other consistencies (Sen et al, 2011 b ); translationabilty: tied to other engineering models (Nebel, 2000); behavior: ability of the representation to simulation behavior (Qian & Gero, 1996); and scalability: support both simple and complex problem types (Chiang et al, 2001). …”
Section: Comparison Across the Criteriamentioning
confidence: 99%
“…scope: the domain for which the function modeling approach is intended (Nagel, Vucovich, et al, 2008);…”
Section: Comparison Across the Criteriamentioning
confidence: 99%
“…Yet many of these databases or repositories are independently operated and do not necessarily support collaboration. Nagel (2007) and Nagel et al (2008) made efforts to move the FB taxonomy to a formal functional basis modeling language. Focusing on the signal flows, it is suggested that using a definitive grammar set improves communication between domains.…”
Section: Engineering Design and Related Workmentioning
confidence: 99%
“…Products are modeled functionally using the Functional Basis [26,40]. The Functional Basis has achieved significant evaluation and acceptance as a repeatable method for representing product function [41][42][43][44]. Actionfunction diagrams highlight those functions of a product in which the user is directly involved.…”
Section: Modeling the Product And The User-product Interfacementioning
confidence: 99%